2006
DOI: 10.1016/j.neurobiolaging.2005.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Activation of brain regions vulnerable to Alzheimer's disease: The effect of mild cognitive impairment

Abstract: This study examined the functionality of the medial temporal lobe (MTL) and posterior cingulate (PC) in mild cognitive impairment amnestic type (MCI), a syndrome that puts patients at greater risk for developing Alzheimer disease (AD). Functional MRI (fMRI) was used to identify regions normally active during encoding of novel items and recognition of previously learned items in a reference group of 77 healthy young and middle-aged adults. The pattern of activation in this group guided further comparisons betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(161 citation statements)
references
References 68 publications
11
147
1
2
Order By: Relevance
“…The more impaired MCI subjects (based on CDR-SB score), showed a pattern of decreased activation in the MTL and functionally connected regions that strongly resembled the pattern seen in mild AD subjects. These results are similar to reports from other groups who have studied more impaired MCI subjects (Machulda et al, 2003;Johnson et al, 2006), and suggests that the variability in published fMRI studies of MCI is likely related to the heterogeneity of subjects within the MCI continuum. Furthermore, our findings are consistent with the theory that the late stage of MCI is likely already very mild AD (Morris and Cummings, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…The more impaired MCI subjects (based on CDR-SB score), showed a pattern of decreased activation in the MTL and functionally connected regions that strongly resembled the pattern seen in mild AD subjects. These results are similar to reports from other groups who have studied more impaired MCI subjects (Machulda et al, 2003;Johnson et al, 2006), and suggests that the variability in published fMRI studies of MCI is likely related to the heterogeneity of subjects within the MCI continuum. Furthermore, our findings are consistent with the theory that the late stage of MCI is likely already very mild AD (Morris and Cummings, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, hippocampal hypoactivation is correlated with the clinical severity of memory loss in aMCI patients [62] . Using an item-based old/new recognition retrieval task, Johnson and colleagues have demonstrated right hippocampal hypoactivation in aMCI patients compared to controls [7] . In contrast, several studies have shown greater hippocampal activation in aMCI patients relative to controls.…”
Section: Task-based Functional Mrimentioning
confidence: 99%
“…Structural and functional changes in the hippocampus are ression and trajectory and the related pathology [7] . Previous studies have indicated that hippocampal atrophy is the most prominent structural hallmark of progression from aMCI to AD [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a common finding in studies of healthy subjects compared with AD or MCI patients is decreased MTL activation in the patients [25,[32][33][34][35][36][37][38][39]. The interpretation is typically that reduced activation in this region corresponds to the memory deficits exhibited by these patients.…”
Section: Mtl Activation: Powers Pitfalls and Possibilitiesmentioning
confidence: 99%